IDENTIFIKASI JAMUR ENDOFIT DAUN JARUM Pinus radiata MENGGUNAKAN METODE EKTRAKSI DNA SECARA LANGSUNG - Istiana Prihatini (Jurnal Pemuliaan Tanaman Hutan, 2014)
Pinus radiata is the major softwood species planted in New Zealand and Australia. Endophyte fungi that have been extensively studied in conifers needles mainly based on fungal isolation and also rarely conducted in Pinus radiata. This study aimed to observe the optimum condition of P. radiata needles sample for direct extraction of fungal DNA and to identify the fungi associated with P. radiata needles in Plenty plantations by a direct PCR approach. Room temperature dried needles produced clear and consistent DNA amplification compare to fresh needles, and needles dried on drying room or drying machine. Capnodiales was the most diverse group and no fungal pathogen detected in this study. DNA sequence data from direct DNA extraction of P. radiata needles provided sufficient discrimination and identification of fungal species.